DISCOVERY LEARNING MODEL IN READING SKILL LEARNING AT MADRASAH ALIYAH AL-UMM: ANALYSIS OF IMPLEMENTATION AND STUDENT RESPONSE - Bela Noviana Dewi; Muassomah Muassomah; Wildana Wargadinata (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
A student who is susceptible to an erroneous understanding of Arabic texts when low reading skills. Therefore, learning reading skills must be done in a good way. This study aims to describe Madrasah Aliyah Al-Umm Malang's implementation of a discovery learning model in her 10th-grade reading comprehension learning and student responses to the application of this learning model. This study used a descriptive qualitative method. The results of this study suggest that the steps for applying the discovery learning model to learning reading skills are to provide suggestions, identify problems, collect data, process data, and prove and generalize. Indicates that there are Student responses to the use of discovery learning models that demonstrate that discovery learning models can train different aspects, starting with independence, cooperation, and self-confidence. In theory, researchers hope their research can contribute to the development of science, especially in education related to teaching Arabic in general and reading comprehension in particular. The results of this research will also provide new knowledge for researchers and readers. In the meantime, the researcher hopes his work will help Arabic language teachers choose appropriate and effective learning models to apply to their literacy materials.